Sistema de control informático para la administración del centro médico comunitario de especialidades “Vicente Izquierdo” del Club de Leones del cantón Quevedo - Sánchez Morán, Leonardo David (2013)
The investigative work present consists in the elaboration of a System for the administration of specialty community health center “Vicente Izquierdo " Lions Club of Canton Quevedo. The system will be an important tool to control unified patient information and in turn control and structure information in medical procedures that are generated in the same, allowing the optimization of the resources. The administrative system has been developed using the following tools:  Microsoft Visual Studio 2010.  Microsoft SQL Server Management Studio 2008. Specifically, we used the OpenUP object-oriented method, which consists of several stages which are: Inception, Elaboration, Construction and Transition, Aimed at management and software development. Iterative, agile and incremental important at every stage of the software that is made, focusing on the architecture early to minimize risks and organize development. The User Manual is aimed at people who will use the system, which is explained how different users have to register their username and password to use its corresponding interface and then to add or edit data. The system will be an essential support for information management and centralized medical center in the registry of treatment that will give the patient as it is, the diagnosis of disease, monitoring of medications and lab tests. Also incorporated into the system who sees the patient and when it does. To later get reports immediately or when required.